Power Board : Type 5125 - Technical Description - Hps SystemTechnik
With the Power board hps Systemtechnik (Type 5125) offers a demonstration and training system with which experiments covering the whole field of power eclectronics can be carried out. All important single - and three - phases current coverter circuits can be conected with protective extra-low voltage. The power in all circuits is controlled by a DC volltage in +-10 V range. This make it possible to intergrate the Power board in complete control circuits as well, for example with the Pid board (type 5120) or commercial Pid control.....